2016
DOI: 10.2298/abs141218006s
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and genotoxicity of iron oxide nanoparticles: An in vitro biosafety study

Abstract: With the development of nanotechnology and the wide use of iron oxide nanoparticles, it has become necessary to assess the potential adverse biological effects of magnetite. This study investigated the cytotoxicity, genotoxicity and oxidative damage of different concentrations of magnetite (0 to 1000 mg/L) in human whole blood cultures. After supplementation of magnetite, the blood samples were incubated for 72 h. Cell viability was assessed by the 3-(4,5-dimethylthiazol-2-yl) 2,5-diphenyltetrazolium bromide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Conflicting evidence regarding the toxicity of IONPs has been reported in in vitro and in vivo studies [ 213 , 214 , 215 , 216 ]. Factors inherent to nanosystems involving IONPs tend to directly interfere with their toxicity.…”
Section: Ionps Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicting evidence regarding the toxicity of IONPs has been reported in in vitro and in vivo studies [ 213 , 214 , 215 , 216 ]. Factors inherent to nanosystems involving IONPs tend to directly interfere with their toxicity.…”
Section: Ionps Toxicitymentioning
confidence: 99%
“…Positively charged IONPs were shown to be more toxic, since they undergo nonspecific interactions and adsorptive endocytosis with the negatively charged cell membrane, thus increasing their intracellular accumulation and affecting cell membrane integrity [ 218 ]. Other factors such as concentration, type of coating, form of administration, as well as the cell line may explain the different results for IONPs toxicity [ 21 , 22 , 23 , 25 , 26 , 66 , 71 , 72 , 96 , 97 , 98 , 163 , 214 , 215 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 ], as shown in Table 1 .…”
Section: Ionps Toxicitymentioning
confidence: 99%
“…16 have also reported that magnetic IONPs cause cellular cytotoxicity to rat lymphocytes via ROS generation in a dose and time-dependent manner 16 . It was also reported that IONPs induced oxidative stress and decreased cell viability of human hepatocytes and human lymphocytes 13,38 . Our study also reported that the exposure of IONPs to rat lymphocytes reduced cell viability in a dose-dependent manner after 24 h, and at the highest concentration (800 μg/ml), the cell viability decreased up to 3 folds.…”
Section: Discussionmentioning
confidence: 94%
“…The previous studies related to toxicity of IONPs have created a lot of ambiguities 39 . An increase in micronucleus frequency was observed in human peripheral blood after IONPs exposure in a dose-dependent manner 38 . Similarly, oxidative stress-induced DNA damage was also observed after an intraperitoneal administration of IONPs in mice 18,40 .…”
Section: Discussionmentioning
confidence: 99%
“…The study performed by Kouchesfehani, Kiani, Rostami, and Fakheri () demonstrated that IONP cytotoxicity was mainly dose‐dependent and a concentration of 10 μg/ml already reduced the proliferative activity of mouse embryonic stem cells. Conflicting data exist regarding the cytotoxicity of IONPs (Sonmez et al, ) , (Xu et al, ). It has been shown that not only the dose but also nanoparticle size and shape play an important role in cell toxicity (Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%